E-ADA activity in erythrocytes of lambs experimentally infected with Haemonchus contortus and its possible functional correlations with anemia - Da Silva A.S.* (2013)
The aim of this study was to evaluate the ecto-adenosine deaminase (E-ADA) activity in erythrocytes of lambs experimentally infected with Haemonchus contortus, correlating it with the degrees of anemia of the experimental animals. A total of 14 healthy lambs, with negative fecal exam for parasites, were to carry out the present study. They were divided into two groups, composed by seven animals: Group A represented the healthy animals (uninfected), while in Group B the animals were infected with 15,000 larvae of H. contortus. Blood was drawn on the days 15, 45 and 75 post-infection (PI) in order to perform the hematological analysis, as well as the mensuration of E-ADA activity in erythrocytes. Parasitological stool exam were performed on the same days mentioned above to follow up the evolution of the infection, as well to determine the number of eggs per gram of feces (EPG). On day 15. PI, the animals presented negative EPG and there was not significant (P>. 0.05) difference between groups in relation to E-ADA activity and hematologic parameters. Animals in Group B had positive EPG for helminths on days 45 and 75 PI, accompanied by varying degrees of anemia, when compared to Group A. At the same periods E-ADA activity was significantly (P<. 0.05) increased in the erythrocytes of animals of Group B when compared with the not-infected ones. Statistically, there was a negative correlation (P<. 0.01) between activity E-ADA in erythrocytes and hematocrit on days 45 (r= -0.76) and 75 (r= -0.85). PI. Based on these results and in the scientific literature, it is possible to conclude that the E-ADA may participate on mechanisms related with the pathogenesis and host response against anemia caused by H. contortus. © 2013 Elsevier Ltd.